Bravely - Stiefvater, Maggie, 1981- (Los Angeles : Disney Press, 2022)
When a supernatural being appears in DunBroch on Christmas Eve with the intent of demolishing the realm, Princess Merida, under the watchful eyes of the gods, embarks on a series of epic journeys to save those she loves from ruin.
Keywords: Princesses -- Juvenile fiction; Paranormal fiction; Gods -- Juvenile fiction; Goddesses -- Juvenile fiction; Young women -- Juvenile fiction; Kings and rulers -- Juvenile fiction; Fairy tales; Adventure stories; Princesses -- Fiction; Supernatural -- Fiction; Gods -- Fiction; Goddesses -- Fiction; Young women -- Fiction; Kings and rulers -- Fiction; Fairy tales; Adventure and adventurers -- Fiction; Action and adventure fiction; Fantasy fiction; Fairy tales; Novels